2014
DOI: 10.4014/jmb.1401.01023
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of CTX-M-Type Extended-Spectrum Beta-Lactamase-Producing Diarrheagenic Escherichia coli Isolates in the Republic of Korea During 2008-2011

Abstract: To characterize the extended-spectrum beta-lactamases (ESBLs) in diarrheagenic Escherichia coli from Korea in 2008-2011, we screened seven enterotoxigenic E. coli (ETEC) and one enteroaggregative E. coli (EAEC) that produce ESBLs from a nationwide survey. All eight isolates produced CTX-M-type ESBLs, including CTX-M-12 (n = 4), CTX-M-14 (n = 2), and CTX-M-15 (n = 2). PCR-based replicon typing indicated that the blaCTX-M-12 genes of four ETEC isolates were carried on a conjugative IncF plasmid, whereas the blaC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 26 publications
(28 reference statements)
1
19
0
1
Order By: Relevance
“…In this study, 28 of 29 ESBL-EC isolates had CTX-M genotypes, just as CTX-M ESBLs have increased in occurrence worldwide since the 2000s [60]. Although genotypes of our ESBL-ECs were diverse, CTX-M group 1 (bla CTX-M-1 , bla CTX-M-3 , bla CTX-M-15 , bla CTX-M-55 ) and CTX-M group 9 (bla CTX-M-14 , bla CTX-M-27 , bla CTX-M-65 ) were prevalent types, which was consistent with the findings of previous studies in Korea [25][26][27][28]30,32,52,61,62]. The most predominant CTX-M genotype was CTX-M-55, which is a variant of globally emerging CTX-M-15, and it varies by a single amino acid substitution (Ala77→Val) that contributes to enhancing the enzymatic activity [60,63].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, 28 of 29 ESBL-EC isolates had CTX-M genotypes, just as CTX-M ESBLs have increased in occurrence worldwide since the 2000s [60]. Although genotypes of our ESBL-ECs were diverse, CTX-M group 1 (bla CTX-M-1 , bla CTX-M-3 , bla CTX-M-15 , bla CTX-M-55 ) and CTX-M group 9 (bla CTX-M-14 , bla CTX-M-27 , bla CTX-M-65 ) were prevalent types, which was consistent with the findings of previous studies in Korea [25][26][27][28]30,32,52,61,62]. The most predominant CTX-M genotype was CTX-M-55, which is a variant of globally emerging CTX-M-15, and it varies by a single amino acid substitution (Ala77→Val) that contributes to enhancing the enzymatic activity [60,63].…”
Section: Discussionsupporting
confidence: 92%
“…Since whole-genome sequencing (WGS) has become affordable and facilitates the acquisition of useful information regarding multiple AMR genes, genomic mutations, and higher-resolved microbial typing from a single assay, some countries, including the USA, have already conducted WGS-based AMR surveillance [22]. A number of studies have reported the prevalence and characteristics of ESBL-EC from humans and food-producing animals in Korea because of the importance of such ESBL-ECs from a public health perspective [23][24][25][26][27][28][29]. However, few studies have reported the prevalence and characteristics of ESBL-ECs in retail meat in Korea [30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…1 and Supplementary Table S2. Most reports of these alleles have come from Asia, 24,52,58,65,66 with a few isolated accounts from Africa, 23 Europe, 8,34 Australia, 67 South America, 17 Russia, 45 and Canada. 1 Thus, it would appear that this study represents the first report of many CTX-M group 1 alleles in the United States.…”
Section: Discussionmentioning
confidence: 99%
“…Escherichia coli (E. coli) is the predominant facultative anaerobe and commensal microbiota in the mammalian gastrointestinal gut; and some strains can cause severe diarrhea illnesses in humans [1,2]. Various classes of antibiotics have been used to treat diarrhea caused by Diarrheagenic E. coli (DEC) and their continued usefulness is limited by the acquisition of resistance mechanisms in the bacteria [3].…”
Section: Introductionmentioning
confidence: 99%